Modélisation heuristique de la criticité des basses eaux en région méditerranéenne - Ingrid Canovas; Philippe Martin; Sophie Sauvagnargues (Physio-Géo)
The expected impacts of climate change on water supplies give rise to many questions about the emergence of situations of tension between resources and uses, especially for territories already fragile hydrological regime. In France, the area subject to the Mediterranean climate is particularly concerned by the water availability issue during summertime, because it is a hot and sparsely watered area and because it attracts more temporary and permanent people every year. Thus, one can wonder how the risk of water scarcity is structured and how the evolution of its components can lead to a critical situation, in which the system’s state generating the risk can be changed. Such a reflection should then focuses on the advent of a critical situation: dynamic balance, technical aspects, regulatory, policy, etc. In our purposes, we are intending to develop a methodology allowing a chronological and probabilistic modeling of the criticity of low flows through kindenograms (from kindunos, danger). We therefore propose to decline this approach for low flows situations, defined as a delicate balance, at both particular time and place, between the available water resource and the combined environmental and societal demand. The low flows' state, conditioned by natural and human forcings, would then translate an "hydric deficiency", to satisfy at least one water use, over short or long periods.